2021
DOI: 10.1186/s12889-021-10599-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic factors of time to first abortion after sexual debut among fragile state Congolese women: a survival analysis

Abstract: Background Despite the common restrictive abortion laws, abortion remains widespread in sub-Saharan Africa (SSA) countries. Women still utilize abortion services and put their lives and health at risk because abortion can only be procured illegally in private facilities such as mid-level or small patent medicine store that may be manned by unskilled providers or through a non-medicated approach. The objective of this study was to investigate the prevalence of abortion, the reasons women had abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The median time (years) to contraceptive uptake was used to determine timing of contraceptive initiation using the Kaplan–Meier survival analysis. 33 We conducted multivariable logistic regression to determine the factors associated with contraceptive use. Analyses were conducted using Stata Version 14 (StataCorp 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The median time (years) to contraceptive uptake was used to determine timing of contraceptive initiation using the Kaplan–Meier survival analysis. 33 We conducted multivariable logistic regression to determine the factors associated with contraceptive use. Analyses were conducted using Stata Version 14 (StataCorp 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have established a strong association between contraception and induced abortion practices among women [ 37 , 40 , 42 44 ] and this study was an exception. Our findings revealed that women using contraceptives at the time of conception were more likely to have engaged in repeat induced abortion relative to those who were not using contraceptive at the time of conception.…”
Section: Discussionmentioning
confidence: 73%
“…This study found a higher likelihood of repeat induced abortion among women who had attained middle levels of education compared to those with no formal education. While some earlier studies reported contrary results [ 1 , 7 , 36 , 38 ], others found similar findings [ 33 , 37 , 40 ]. Studies that found lower rates of repeated induced abortion among low educated women argued that a low level of education is strongly associated with a lower use of contraceptives, which leads to unintended pregnancies and subsequent abortion [ 33 ].…”
Section: Discussionmentioning
confidence: 81%